Fontes potássicas na produção do pimenteiro em substrato fertirrigado - Abrahão, Camila [UNESP] (2015)
Excess fertilizer can cause damage in sweet pepper cultivation and to the environment. Therefore, the choice of fertilizer and the application of a balanced nutrient solution are essential for the production and quality of the final product. Thus, the aim of the present study was to evaluate the effects of increasing potassium fertilizer, using different potassium sources and doses in the production of fertirrigated sweet pepper grown in substrate under greenhouse conditions as well as monitor the nutritional status of pepper through methods alternative. The characteristics evaluated were: EC and pH of the substrate solution, nitrate and potassium levels in the solution of the substrate and the sap of plants, macro and micronutrients in the leaf dry mass, SPAD index, number of total and marketable fruit, total production and commercial fresh mass, length and diameter of the fruits and the correlations between these variables. The experiment was conducted under 4 experimental design of randomized blocks in a factorial 4 x 2 + 1, constituting 9 treatments, with four repetitions. The treatments consisted of two sources potassic (KCl and K2SO4), four potassium doses (125, 250, 375 and 500 mg L-1) and more control (0 mg L-1). It was observed that the dose of 300 mg L-1 K, regardless of the source used, higher total production and commercial hybrid sweet pepper Platero. The EC of treatment with KCI has reached value of 5.0 dS m-1, while with K2SO4 the maximum value was 3.5 dS m-1, both the higher dose. The application of KCl increased number of fruits compared to K2SO4. Treatment with K2SO4 presented to both the 75 and 165 DAT, higher concentration of poatassium on the dry weight of leaves and of sulfur to DAT 165. A higher concentration of NO3- in the substrate solution occur with K2SO4 relative to KCl to 75 DAT, and to 165 DAT higher concentration of potassium in the substrate solution in the same ...